From bad to cursed eaudiobook - Harper, Lana (Witches of Thistle Grove, 2022)
Opposites attract in this wickedly charming rom-com by Lana Harper, New York Times bestselling author of Payback’s a Witch . Wild child Isidora Avramov is a thrill chaser, adept demon summoner, and—despite the whole sexy-evil-sorceress vibe—also a cuddly animal lover. When she’s not designing costumes and new storylines for the Arcane Emporium’s haunted house, Issa's nursing a secret, conflicted dream of ditching her family’s witchy business to become an indie fashion designer in her own right.  But when someone starts sabotaging the celebrations leading up to this year’s Beltane festival with dark, dangerous magic, a member of the rival Thorn family gets badly hurt—throwing immediate suspicion on the Avramovs. To clear the Avramov name and step up for her family when they need her the most, Issa agrees to serve as a co-investigator, helping none other than Rowan Thorn get to the bottom of things. Rowan is the very definition of lawful good, so tragically noble and by-the-book he makes Issa’s teeth hurt. In accordance with their families’ complicated history, he and Issa have been archenemies for years and have grown to heartily loathe each other. But as the unlikely duo follow a perplexing trail of clues to a stunning conclusion, Issa and Rowan discover how little they really know each other… and stumble upon a maddening attraction that becomes harder to ignore by the day.